2000
DOI: 10.1023/a:1006249016103
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Measurement of nitrogen dioxide using passive diffusion tube over 22 months in Cambridge, U.K. are analysed as a function of sampler exposure time, and compared with NO2 concentrations obtained from a co-located chemiluminescence analyser. The average ratios of passive sampler to analyser NO2 at a city centre site (mean NO2 concentration 22 ppb) are 1.27 (n = 22), 1.16 (n = 34) and 1.11 (n = 7) for exposures of 1, 2 and 4-weeks, respectively. Modelling the generation of extra NO2 arising from chemical reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
6
21
0
Order By: Relevance
“…For comparison, the median exposure-averaged analyser NO x /NO 2 ratio was 2.1 across all sites, and 2.2 and 2.0 for the Haymarket and Queen's Street sites, respectively. The data therefore provide further evidence of intrinsic over-read of NO 2 by PDT consistent with within-tube oxidation of a proportion of the NO also present at the exposure location, 10,11,16 and confirms the problem of using zero bias as a measure of accuracy.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…For comparison, the median exposure-averaged analyser NO x /NO 2 ratio was 2.1 across all sites, and 2.2 and 2.0 for the Haymarket and Queen's Street sites, respectively. The data therefore provide further evidence of intrinsic over-read of NO 2 by PDT consistent with within-tube oxidation of a proportion of the NO also present at the exposure location, 10,11,16 and confirms the problem of using zero bias as a measure of accuracy.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, an advantage of one week exposures is that the confounding effect of decreasing PDT NO 2 values with exposure duration, which may well be variable, should be minimised. 11 General linear modelling (GLM) in Minitab v.14 was used to test for significant factors acting on the two dependent variables %RSD and CAPTURE being investigated. The full GLM comprised: (a) the three factors 'Application Method', 'Solvent' and '%TEA' as the main-effect fixed factors under test; (b) the three pairwise combinations of these factors to test for significant interactions; (c) the two factors 'Analyst' and 'Exposure site' as additional main-effect random factors i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The authors attributed this to additional wind-induced positive bias at this site, supported by the observation that the co-located NO x PDT tubes (which will not be subject to within-tube chemical bias because the reaction converts between NO and NO 2 ) also had a positive bias of around 50%. Allowing for the possibility also of an exposure-duration-dependent negative bias over one-week of~8%, based on earlier work [47], the authors concluded that wind bias at this site could have been as high as 55-60%. They noted that these particular tubes were deployed in an exposed location, mounted at 3 m height without shelter on an air intake duct in the middle of a relatively open square, in one of the UK's windiest urban areas.…”
Section: Field Studiesmentioning
confidence: 94%
“…The model overestimations were subsequently compared against real PDT exposures at urban background sites in Edinburgh [46] and Cambridge [47], with average positive biases due to within-tube chemistry across all exposures at each location of 22% and 31%, respectively. The former study also showed that positive bias was lower for PDTs constructed of quartz glass, which transmit wavelengths for NO 2 photolysis, compared with standard acrylic PDTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation